Pengaruh Pola Asuh Ibu terhadap Kecerdasan Sosial Anak Usia Dini di TK Kenanga Kabupaten Bandung Barat - Robbiyah Robbiyah; Diyan Ekasari; Ramdhan Witarsa (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2018)
The purpose of this research is to determine the effect of early child social intelligence based on the dominant mother pattern in the family. This research is very important to know the social development of early childhood as a whole. Social intelligence is enough to determine the ability of early childhood to foster self-concept and control emotions in order to adjust themselves in the social environment. The development of social intelligence is also strongly influenced by the upbringing and encouragement of the mother, the extent to which the success of mother's upbringing is the extent of mother's involvement and role in the lives of her children. Each mother has her own way of helping her children grow. The formulation of the research problem is how the influence of mother care pattern toward social intelligence of early child in Kenanga Kindergarten of West Bandung Regency. The research method used is qualitative research method by using observation and interview instruments, while data analysis using data reduction phase, data model, and conclusion. The results obtained that mother care pattern to educate children in kindergarten Kenanga is democratic and permissive parenting in developing social intelligence early childhood in West Bandung Regency.